Carabid population in a crop rotation system in northern ltaly (Bollettino di zoologia agraria e bachicoltura, 2024)
A four year research (1989-92) has been carried out in northern Italy in fields in which crop rotation is applied (tomato, winter wheat and alfalfa), to assess the influence of different crops on the composition of ground beetle population. A clear influence of the crop has been observed. In tomato fields 69,2% of insects caught were Steropus melas, followed by Pseudophonus rufipes (12,8%). In cereal field the most abundant species have been Poecilus cupreus (49,2%), S. melas (13,3%) and Anchomenus dorsalis (6,3%). Alfalfashowed a more balanced dominance figure, with Harpalus distinguendus (30,7%), S. melas (19.8%), Brachinus sclopeta (19,8%) and P. rufipes (12,4%). In cereal fields zoophagous (80,5%) and spring breeder (75%) species were markedly prevailing, as much as zoophagous (83,9%) autumn breeder (87,5%) in tomato; in alfalfa, less than half (47,2%) of the species are zoophagous and spring breeders were 64,9%.
Keywords: Carabidae; populations; agriculture; tomato; cereals; alfalfa